Regulation of photosynthetic carbon metabolism - Anderson, Louise (Henry Stewart Talks, 2007)
Photosynthetic CO2 fixation, Regulation of CO2 fixation, Mg++ effects, pH effects, Light activation, the thioredoxin system, Rubisco activase, Rubisco, O2 competes with CO2, Rate-limiting enzymes, Enzyme-enzyme interaction and substrate channeling